Penanaman Nilai Nilai Moral dalam Pembelajaran Alfiyyah di Pondok Pesantren - Abdullah Al Mahfudh (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
This research is basically to describe the application of inculcating moral values ​​in Alfiyyah learning at the Raudlatul Muttaqin Islamic Boarding School Talun Sidogembul Sukodadi Lamongan. With this research, it is hoped that appropriate methods and systems can be revealed in the process of inculcating moral values ​​in Alfiyyah learning in other educational places. Considering that Alfiyyah is a book that explains nahwu and sorof, this study also wants to reveal the method, basis and reasons for interpreting Alfiyyah's verses as a medium for moral cultivation. Furthermore, this study also seeks to explore the relationship between Alfiyyah's moral values ​​and established arguments such as the Qur'an, hadith and maqalah from the ulama. The research that took the subject of Kiai and santri who were studying Alfiyyah at the Raudlatul Muttaqin Islamic boarding school was a descriptive study using a qualitative approach. The results show that the process of inculcating moral values ​​through Alfiyyah learning includes: storytelling, lectures, habituation, discussion, example, analysis of actual problems that develop in society, inculcation of contextual educational values ​​and strengthening of previous moral values. already owned by the students.